SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

The Relationship Between Perceived Discrimination and Reported Nutrient Intake Among Pregnant Individuals of Minoritized Racial and Ethnic Groups - Tatyana Johnson; Ann K. Kan; Lauren B. Bonner; Linda Van Horn; Kiarri N. Kershaw; William A. Grobman; Karen L. Lindsay; Michelle P. Debbink; Brian M. Mercer; David M. Haas; George R. Saade; Uma Reddy; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Shelf break exchange processes influence the availability of the northern shortfin squid, Illex illecebrosus , in the Northwest Atlantic - Sarah L. Salois; Kimberly J. W. Hyde; Adrienne Silver; Brooke A. Lowman; Avijit Gangopadhyay; Glen Gawarkiewicz; Anna J. M. Mercer; John P. Manderson; Sarah K. Gaichas; Daniel J. Hocking; Benjamin Galuardi; Andrew W. Jones; et al. (Fisheries Oceanography, 2023)
The United States Northern Shortfin squid fishery is known for its large fluctuations in catch at annual scales. In the last 5 years, this fishery has experienced increased availability of Illex illecebrosus along the Northeast US continental shelf (NES), resulting in high catch per unit effort (CPUE) and early fishery closures due to quota exceedance. The fishery occurs within the Northwest Atlantic, whose complex dynamics are set up by the interplay between the large‐scale Gulf Stream, mesoscale eddies, Shelfbreak Jet, and shelf‐slope exchange processes. Our ability to understand and quantify this regional variability is requisite for understanding the availability patterns of Illex , which are largely influenced by oceanographic conditions. In an effort to advance our current understanding of the seasonal and interannual variability in this species' relative abundance on the NES, we used generalized additive models to examine the relationships between the physical environment and hotspots of productivity to changes in CPUE of I. illecebrosus in the Southern stock component, which comprises the US fishery. Specifically, we derived oceanographic indicators by pairing high‐resolution remote sensing data and global ocean reanalysis physical data to high‐resolution fishery catch data. We identified a suite of environmental covariates that were strongly related to instances of higher catch rates. In particular, bottom temperature, warm core rings, subsurface features, and frontal dynamics together serve as indicators of habitat condition and primary productivity hotspots, providing great utility for understanding the distribution of Illex with the potential for forecasting seasonal and interannual availability.

Mechanisms and models for industry engagement in collaborative research in commercial fisheries - Matthew R. Baker; Robert Alverson; Ruth Christiansen; Keith Criddle; Danny Eilertsen; Robert J. Foy; John Gauvin; Scott E. Goodman; Leigh Habegger; Bradley P. Harris; Nicole Kimball; Anna Malek Mercer; et al. (Frontiers in Marine Science, 2023)
Data and insights from fishers are essential sources of information to advance understanding of fishery and ecosystem dynamics. Incorporating fisher and industry knowledge holds prospects for improving marine science and fisheries management. We address cooperative research in the context of collaboration between fishers, scientists, industries, universities, and agencies to develop applied research to understand marine ecosystems, inform fishery management, enhance sustainability, govern resource use, and investigate social-economic dynamics. We leverage the insights of more than 100 research scientists, fisheries managers, industry representatives, and fishers to outline actionable recommendations for effective approaches and mechanisms to integrate industry data, perspectives, and insights in fisheries science. We also highlight opportunities and address challenges and limitations to such collaboration.

Bringing in the experts: application of industry knowledge to advance catch rate standardization for northern shortfin squid (Illex illecebrosus) - Anna J. M. Mercer; John P. Manderson; Brooke A. Lowman; Sarah L. Salois; Kimberly J. W. Hyde; Jeffrey Pessutti; Andrew W. Jones; Robert Ruhle; Bill Bright; Troy Sawyer; Meghan Lapp; Jeff Kaelin; et al. (Frontiers in Marine Science, 2023)
Sources of fisheries information outside of fishery-independent surveys (e.g. fishery-dependent data) are especially valuable for species that support productive fisheries and lack reliable biological information, such as the northern shortfin squid ( Illex illecebrosus ). Fishery-dependent data streams are available for most species, however collaboration with industry members is critical to ensure that these fishery-dependent data are collected, applied, and interpreted correctly. Despite the need for collaboration and the frequency that fishery data are used in scientific research, there is limited literature on the structure of interactions and knowledge sharing that inform the analysis and application of fishery data. Between 2019 and 2022, a group of researchers collaborated with members of the northern shortfin squid fishing industry to bring together research data sets and knowledge from harvesters and processors to better describe the fishery dynamics, distribution, life history, and oceanographic drivers of the species. The collaboration focused on developing custom standardized fishery catch per unit effort (CPUE) indices to provide indicators of population trends that accounted for the impacts of technical and economic aspects of harvesting, processing and marketing on fishing effort, selectivity and landings of northern shortfin squid. We describe the methods used to inform and interpret the CPUE analyses, focusing on novel structure of interactions we had with industry members, and suggest best practices for integrating industry knowledge into CPUE standardization. The information shared and research products produced through this science-industry research collaboration advanced understanding of northern shortfin squid population and fishery dynamics, and contributed directly to the 2022 stock assessment and management process. Given the complex and stochastic nature of the northern shortfin squid population and fishery, we found it critical to maintain open communication and trust with processors and harvesters, who have unique insight into the factors that may be driving changes in catch, landings, and productivity of the valuable resource species.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Scale‐dependent patterns of metacommunity structuring in aquatic organisms across floodplain systems - Fernando M. Lansac‐Tôha; Luis M. Bini; Jani Heino; Bianca R. Meira; Bianca T. Segovia; Carla S. Pavanelli; Claudia C. Bonecker; Claudia P. de Deus; Evanilde Benedito; Geziele M. Alves; Gislaine I. Manetta; Juliana D. Dias; et al. (Journal of Biogeography, 2021)
Aim Evaluating how groups of organisms vary in dispersal capability and how environmental, spatial and temporal signals vary across multiple scales is critical to elucidating metacommunity theory. We examined whether the relative contributions of environmental, spatial and hydrological factors have different effects on organismal groups with different dispersal abilities at three spatial scales, and how this knowledge contributes to our understanding of metacommunity dynamics. Location Four major Brazilian floodplains, with the largest distance among them of 2,300 Km. Taxon 10 aquatic organismal groups, ranging from bacterioplankton to fish. Methods We sampled lakes connected to the main river in the low‐ and high‐water periods of each floodplain between 2011 and 2012. Different biological groups were analysed across three hierarchical spatial scales (fine, intermediate and subcontinental) within and between floodplain systems. We applied a series of partial redundancy analyses to estimate the relative contributions of environmental factors, spatial factors and hydrological period for each biological group. Results At the fine spatial scale, predominantly environmental factors and hydrological period structure metacommunities, although less so for microorganisms than for micro‐invertebrates and macro‐organisms. The relative importance of environmental factors increased at the intermediate spatial scale. At the subcontinental scale, the relative importance of spatial factors increased for all biological groups, but environmental factors remained the primary regulators of microorganisms even at the largest scale. Main conclusions This study design allowed us to make more robust inferences about the mechanisms responsible for regulating community structure of distinct biological groups at different spatial scales. Our results suggest that biological groups displaying distinct body size likely determine the spatial extent at which environmental, spatial and hydrological processes prevail as the primary regulators of community structure. These findings are important in guiding the conservation and management of floodplain biodiversity because these systems are naturally highly heterogeneous in space and time.

Northern Shortfin Squid (Illex illecebrosus) Fishery Footprint on the Northeast US Continental Shelf - Brooke A. Lowman; Andrew W. Jones; Jeffrey P. Pessutti; Anna M. Mercer; John P. Manderson; Benjamin Galuardi (Frontiers in Marine Science, 2021)
Northern shortfin squid ( Illex illecebrosus ) have presented a challenge for US fishery management because of their life history traits and broad population distribution. They are characterized by a short semelparous lifespan and high interannual variability in recruitment. Much of the stock resides outside of the boundaries of existing US fisheries surveys and US fishing effort. Based on the annual migration pattern and broad geographic distribution of shortfin squid, it is believed that the US squid fishery in the Mid-Atlantic has not had a substantial impact on the stock; however, recent catches are viewed as tightly constrained by quotas. To better estimate the potential impact of fishing on the resource, we worked with industry representatives, scientists, and managers to estimate the availability of the northern shortfin squid stock on the US continental shelf to the US fishery. Taking a novel analytical approach, we combine a model-based estimate of the area occupied by northern shortfin squid with the empirical US commercial shortfin squid fishery footprint to produce estimates of the area of overlap. Because our method overestimates the fishery footprint and underestimates the full distribution of the stock, we suggest that our estimates of the overlap between the area occupied by the squid and the fishery footprint is a way to develop a conservative estimate of the potential fishery impact on the stock. Our findings suggest a limited degree of overlap between the US fishery and the modeled area occupied by the squid on the US continental shelf, with a range of 1.4–36.3%. The work demonstrates the value of using high-resolution, spatially explicit catch and effort data in a species distribution model to inform management of short-lived and broadly distributed species, such as the northern shortfin squid.

Determining if muscle activity is related to preferred stride frequency during running in the water and on land - Kenji Masumoto; Joshua P. Bailey; John A. Mercer (European Journal of Applied Physiology, 2015)

The New Zealand experience of varroa invasion highlights research opportunities for Australia - Jay M. Iwasaki; Barbara I. P. Barratt; Janice M. Lord; Alison R. Mercer; Katharine J. M. Dickinson (Ambio, 2015)

Analysis of Hydrated Lime Consumption in Circumneutral Underground Coal Mine Drainage Treatment - Brent Means; P. G. Rich Beam; Julia Mercer (Mine Water and the Environment, 2015)

Therapeutic immunomodulation using a virus—the potential of inactivated orf virus - O. Weber; A. A. Mercer; A. Friebe; P. Knolle; H.-D. Volk (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Production and Evaluation of an Antimicrobial Peptide-Containing Wafer Formulation for Topical Application - Noelle H. O’Driscoll; Olga Labovitiadi; T. P. Tim Cushnie; Kerr H. Matthews; Derry K. Mercer; Andrew J. Lamb (Current Microbiology, 2013)

Photoperiod regulates leptin sensitivity in field voles, Microtus agrestis - E. Król; J. S. Duncan; P. Redman; P. J. Morgan; J. G. Mercer; J. R. Speakman (Journal of Comparative Physiology B, 2006)

Mitochondrial DNA variation in the European lobster (Homarus gammarus) throughout the range - A. Triantafyllidis; A. P. Apostolidis; V. Katsares; E. Kelly; J. Mercer; M. Hughes; K. E. Jrstad; A. Tsolou; R. Hynes; C. Triantaphyllidis (Marine Biology, 2005)

Sub-arctic Populations of European Lobster, Homarus gammarus, in Northern Norway - Knut E. Jørstad; Paulo A. Prodöhl; Ann-Lisbeth Agnalt; Maria Hughes; Apostolos P. Apostolidis; Alexandros Triantafyllidis; Eva Farestveit; Tore S. Kristiansen; John Mercer; Terje Svåsand (Environmental Biology of Fishes, 2004)

Understanding Broadscale Wildfire Risks in a Human-Dominated Landscape - Jeffrey P. Prestemon; John M. Pye; David T. Butry; Thomas P. Holmes; D. Evan Mercer (Forest Science, 2002)
Broadscale statistical evaluations of wildfire incidence can answer policy-relevant questions about the effectiveness of microlevel vegetation management and can identify subjects needing further study. A dynamic time series cross-sectional model was used to evaluate the statistical links between forest wildfire and vegetation management, human land use, and climatic factors in Florida counties. Four forest wildfire risk functions were estimated: one for fires regardless of ignition source, and three others for fires of specific ignition sources: arson, lightning, and accident (unintentional anthropogenic). Results suggest that current wildfire risk is negatively related to several years of past wildfire and very recent site prep burning, and risk is positively related to pulpwood removals. The effect of traditional prescribed burning on wildfire risk varies by ignition source. El Niño–Southern Oscillation (ENSO) sea surface temperature (SST) anomalies were also significantly linked to forest wildfire risk, but a measure of the wildland-urban interface was not significant. Although these county-level results hold promise for aggregate risk assessment, modeling at finer spatial and temporal scales might further enhance our understanding of how land managers can best reduce the longer term risk of catastrophic wildfire damages. For. Sci. 48(4):685–693.

Searching for the early benthic phase (EBP) of the European lobster: a trans-European study of cobble fauna - Adrian Linnane; Brendan Ball; John P. Mercer; Ronan Browne; Gro van der Meeren; Halldis Ringvold; Colin Bannister; David Mazzoni; Brian Munday (Hydrobiologia, 2001)

An historical overview of the Republic of Ireland's lobster (Homarus gammarus Linnaeus) fishery, with reference to European and North American (Homarus americanus Milne Edwards) lobster landings - R. M. Browne; J. P. Mercer; M. J. Duncan (Hydrobiologia, 2001)

Littoral Acari of Marion Island: ecology and extreme wave action - P. J. A. Pugh; R. D. Mercer (Polar Biology, 2001)

Elemental composition of human milk from mothers of premature and full-term infants during the first 3 months of lactation - James K. Friel; Wayne L. Andrews; Simon E. Jackson; Henry P. Longerich; Claude Mercer; Allison McDonald; Barbara Dawson; B. Sutradhar (Biological Trace Element Research, 1999)

Lack of an effect of zolmitriptan (Zomig, 311C90) on psychometric task performance: results of a placebo-controlled study in healthy volunteers - A. J. Mercer; R. J. Lamb; P. E. Rolan; M. Gibbens; J. Posner (Psychopharmacology, 1998)

The reactivity of monoclonal antibodies against orf virus with other parapoxviruses and the identification of a 39 kDa immunodominant protein - F. M. T. Housawi; G. M. Roberts; J. A. Gilray; I. Pow; H. W. Reid; P. F. Nettleton; K. J. Sumption; M. H. Hibma; A. A. Mercer (Archives of Virology, 1998)

Prolonged intermittent high intensity exercise impairs neuromuscular performance of the knee flexors - T. H. Mercer; N. P. Gleeson; S. Claridge; S. Clement (European Journal of Applied Physiology, 1998)

Socioeconomic research in agroforestry: progress, prospects, priorities - D. E. Mercer; R. P. Miller (Agroforestry Systems, 1997)

s 59th annual meeting Potato Association of America - D. E. Hudson; M. D. Volz; B. B. DePhillips; Gene A. Mathia; Frank Haynes; N. A. Wynn; Allen E. Abrahams; Lewis A. Schaper; Paul H. Orr; Earl C. Yaeger; Combs Joseph; Robert L. Mercer; et al. (American Journal of Potato Research, 1975)

The influence of ammonium nitrate on the fine structure of nodules of medicago tribuloides Desr. and trifolium subterraneum L. - P. J. Dart; F. V. Mercer (Archives of Microbiology, 1965)

Fine structure changes in the development of the nodules of Trifolium subterraneum L. and Medicago tribuloides Desr. - P. J. Dart; F. V. Mercer (Archives of Microbiology, 1964)

The legume Rhizosphere - P. J. Dart; F. V. Mercer (Archives of Microbiology, 1964)

Development of the bacteroid in the root nodule of barrel medic (Medicago tribuloides Desr.) and subterraneum clover (Trifolium subterraneum L.) - P. J. Dart; F. V. Mercer (Archives of Microbiology, 1963)

The intracytoplasmic membrane system of the bacteroids of subterraneum clover nodules (Trifolium subterraneum L.) - P. J. Dart; F. V. Mercer (Archives of Microbiology, 1963)